Cyber Diplomacy - Saeed Seyed Agha Banihashemi (Cyber Diplomacy, 2021)
In the new age of information technology, the great powers no longer rely solely on the armed forces and geographical size and population, etc. Another influential factor has emerged in the world, called information technology, which has made a tremendous impact in all aspects of human life, society and governments. Undoubtedly, international relations and political science will not be ineffective in this regard. Currently, cyber plays has an important role in this field. In this book, while defining the definition of cyber diplomacy and explaining its difference with diplomacy in cyber in different chapters, while explaining the components of cyber diplomacy, its applications are explained and why considered necessary by the diplomats of ministries of foreign affairs. Giving examples of cyber diplomacy in developed countries, I will mention about the damages of not paying attention to cyber diplomacy.